Studying the resonance production cross-section of the heavy vectors within Heavy Vector Triplet model - Obikhod, T.V.; Petrenko, I.A. (Problems of Atomic Science and Technology, 2023)
In the context of TeV-scale extensions of the Standard Model both the experimental data and the construction of phenomenological models for the new heavy bosons searches are used by us. Heavy particles are predicted by the Simplified Model to describe only the on-shell resonance, have to be compared with LHC data. Bosons V’ created and decay according to the process pp‐>V’‐>Vh (V=W, Z) have certain properties that can be modeled within the Heavy Vector Triplet model using the Madgraph computer program. We have calculated the production cross sections of heavy particles using the experimental constraints in the parameter space (cₕ, cf) imposed on the benchmark scenario. The nature of the functional dependence of the cross section on the mass of the new boson, as well as the mechanism for the heavy particle production is studied with variation of the model parameters. У контексті тераелектронвольтних розширень Стандартної моделі нами використовуються як експериментальні виміри, так і побудовані феноменологічні моделі для пошуку нових важких бозонів. Важкі частинки, що передбачені спрощеною моделлю, яка побудована для опису тільки резонансу на оболонці, необхідно порівнювати з даними на LHC. Бозони V’, що утворюються і розпадаються відповідно до процесу pp‐>V’‐>Vh (V=W, Z), мають певні властивості, які можна змоделювати в рамках Heavy Vector Triplet моделі за допомогою комп’ютерної програми Madgraph. Ми розрахували перерізи утворення важких частинок V’ з використанням експериментальних обмежень у просторі параметрів (cₕ, cf), які накладено на еталонний сценарій. Досліджено характер функціональної залежності перерізу при основних параметрах моделі від маси нового бозона, а також механізм народження таких частинок.